(untitled) (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
Using the complex of physico-chemical methods the studied the nature and special features of chemical interaction, thermal transformations (25 – 1000 oC) of structural components in a model system of neodymium and potassium nitrates – systems of nitrates of rare-earth elements and elements of periodic system IA group, ammonium, that at present are widely used in syntheses, technological regulations of creation on their base constructional materials of different designation with the assigned complex of structurally sensitive characteristics. A number of special features and regularities in their joint behavior were discovered. Keywords: neodymium, potassium, nitrates, complexion, coordination compounds, thermal transformations, property.